Contributions of Tax Revenue and Government Expenditure to Sustainable Development Goals in Nigeria - Ubali , Chinatu; Okezie, Stella Ogechukwu; Alpheaus, Ogechi Eberechi; Ihendinihu, John Uzoma (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study empirically examined the effect of tax revenue and government expenditure on sustainable development goals in Nigeria. The ex-post facto research design was adopted using time series data sourced from the Central Bank of Nigeria's statistical bulletin and World Bank database. The study covered 22 years from 2001 to 2021. Descriptive and inferential statistical tools were used in analyzing the data after carrying out unit root tests on the stationarity of the series to avoid obtaining invalid and unauthentic regression estimates. The Vector Error Correction Model (VECM) was applied in analyzing the relationship. The study found that Tax Revenue (TR) exhibited a negative and significant effect on sustainable development goals, while Government expenditure (GEXP) indicated a positive and significant effect on Sustainable Development Goals (SDGIS) in the long run. Furthermore, the study revealed that in the short-run Tax Revenue (TR) and Government expenditure (GEXP) both had a negative effect on the SDGIS in Nigeria. There is need for government to develop strategies to broaden the tax base and bring more entities into the tax net while ensuring equitable contribution. They should also align budget allocations with SDG priorities to ensure tax revenue is directed sustainable development projects. Hence the study recommended that government should channel its resources towards closing up infrastructural deficits while increasing productive units that would enhance the economy and ensure optimal utilization of tax revenue towards sustainable developments in Nigeria especially in the achievement of the Sustainable development goals.